An Analysis on Final Term Test of Pre-Intermediate Level in Healthcare English Program for Midwifery - Sarova Widiawati; R.M. Rizky Wirabrata; Novi Indah Susanthi; Riza Lestari (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to find out to what extent that final-term test of pre-intermediate level in healthcare English program complies to the criteria of good test. A qualitative design with content analysis method was carried out to conduct this study. To analyze the data, the researcher first examined the test items and instructions in both the oral test and final test. After that, the items were classified. Once it was done, the researcher would decide to what extent the test is considered as a good test. The result shows that the test does not fulfill the criteria of a good test since only some of the criteria are complied. The oral test contains only three principles, which are validity, authenticity, and washback. Meanwhile, the same goes to the written test since it only covers validity, authenticity, and washback.